Accessing Rights and Entitlements Under the Withdrawal Agreement: A View From the East of England - Barnard, Catherine; Costello, Fiona (Border Crossing, 2025)
In this commentary we reflect on the citizens’ rights provisions of the Withdrawal Agreement (WA), which came into force on 1 February 2020, and the experiences of low paid (low skilled) EU migrant workers in the East of England in accessing these rights and entitlements. It is well documented that low paid EU citizens do not access/ enforce their rights and entitlements via traditional dispute resolution routes. The Independent Monitoring Authority (IMA) was, in fact, set up to assist EU nationals in the UK not with enforcement as such but with (i) Monitoring how UK public bodies are protecting the rights of EU and EEA EFTA citizens and their family members; and (ii) Promoting the effective implementation of citizens’ rights. They (the IMA) also have powers to launch inquiries and take legal action when appropriate. We have been working with two charities, GYROS (in Great Yarmouth, Norfolk) and PBIC (in 12 Bedford, Bedfordshire), who carried out a survey (drawing on the IMA’s annual citizens’ rights 13 survey) to understand the experiences of low skilled migrant workers from ‘hard to reach’ 14 communities. Using this data, we wanted to understand first, whether low skilled EU nationals are having difficulties accessing their rights (monitoring), and second, whether there are issues with the implementation of those rights (implementation)? The data from the survey suggests that low skilled EU citizens are still having difficulty gaining access to their rights. This is for two reasons: (1) lack of awareness of those rights and (2) some lack of trust in public bodies to fulfil these obligations. These findings are relevant to the full implementation of the Withdrawal Agreement and citizen’s rights to which the UK has committed to faithfully implement (where failure to do so can result in proceedings brought by the EU Commission). This article therefore aims to contribute to the evolving area of scholarship around understanding the experiences of EU citizens in the UK post Brexit by including those ‘harder to reach’ communities and their experiences of accessing rights and entitlements under the WA.